Perempuan Dalam Profesi Marketing (Studi Kasus Perilaku Komunikasi Pemasaran Yang Dilakukan Karyawan Perempuan Di PT. Hatsonsurya Electric) - Devi Siang Hari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Bhayangkara Surabaya, 2023)
Women who work in the marketing field have their own behavior in the process of delivering communications internally and externally to the company. The purpose of this study is to find out how the marketing communication process is carried out by female employees and what factors are behind the communication process being formed. This type of research is a case study with a qualitative descriptive approach using interview, observation, and documentation techniques. The results of the study show that the communication process that occurs is non-verbal with a structural communication style and there are three factors behind the occurrence of this communication process, namely the gender factor, knowledge factor, length of service factor. This research is expected to provide new knowledge about the other side that women have in carrying out their duties and functions in maintaining a good company image through marketing